HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP TERHADAP PERILAKU PENGGUNAAN MASKER PADA KARYAWAN GERBANG TOL BEKASI BARAT TAHUN 2014 - Laras Indri Palupi, (2014)
Increased motor vehicle on the highway as a means of human transport constant will be proportional to the increase in air pollution to the surrounding environment. Employees toll gate is one vulnerable group who may be exposed to diseases caused by exposure to air pollutants every day. One of the prevention is to use Personal Protective Equipment (PPE), a mask. This study aims to determine the relationship between knowledge and attitudes towards the use of masks in the behavior of employees Bekasi Barat toll gate in 2014. The study is a descriptive analytic cross- sectional design. Large sample of 92 respondents and taken with probability sampling technique with stratified random sampling method. Data were analyzed using the chi square test with significance (p <0.05). The results showed that there is a relationship (p <0.05) between the knowledge of the behavior of the use of masks (p = 0.000) and there was no correlation between attitude and behavior of the use of masks (p = 0.077) in West Bekasi toll gate employees in 2014.